KAJIAN DESKRIPSI PELAKSANAAN OTONOMI DAERAH ORGANISASI PERANGKAT DAERAH (OPD) - Widyatama, Arif (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2023)
This article aims to describe the Regional Apparatus Organization (OPD) of Palu City. The implementation of regional autonomy has been implemented effectively since January 1 2002. The implementation of regional autonomy is a policy that is considered very democratic and fulfills the aspects of true government decentralization. This research uses a descriptive approach by explaining in detail the conditions of OPD in Palu City. For regional governments, DAU receipts through transfers from the central government are a source of funding that can be used to carry out their authority, while funding shortfalls are expected to be recovered through their own funding sources, namely through receipts from PAD sources. However, in reality, transfers from the central government are the main source of funds for regional governments to finance their main day-to-day operations or regional expenditure, which regional governments reportedly take into account in the APBD.